The Relationship Between Knowledge, Attitudes Of Pregnant Women And Husband's Support For Antenatal Care Examinations At The Leo Leo Health Center - Cece Indrawati; Anik Sri Purwanti; Rifzul Maulina (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Generally, pregnancy develops normally until delivery, but some pregnancies can be at risk in certain circumstances so that pregnancy checks (antenatal care) are needed. Some pregnant women do not do ANC (K1 and K4) allegedly due to lack of husband's support, lack of knowledge and negative attitudes about ANC. To determine the effect of husband's support, knowledge, and attitudes of pregnant women on Antenatal Care Visits. This type of research is an analytical survey with a Cross Sectional approach. The research was conducted at the Leo Leo Health Center, with the research time in Desember 2024. The population in this study were all pregnant women in the third trimester of the Leo Leo Health Center, namely 38 people and all of them were used as samples (total population). Data were analyzed univariately, bivariately with the chi-square test, and multivariately using multiple logistic regression tests at a 95% confidence level (=0.05). The study showed that the majority of ANC visits by pregnant women were not up to standard (52.6%), those up to standard (47.4%). Pregnant women's ANC visits at the Leo Leo Health Center were influenced by husband's support (p = 0.033), and knowledge (p = 0.004), while attitude had no effect (p = 0.156). The knowledge variable was the most dominant variable influencing ANC visits. Pregnant women with good knowledge were 13.7 times more likely to make ANC visits according to standards compared to pregnant women with less knowledge. The probability of pregnant women making ANC visits according to standards was 90.99% if husband's support was good and mother's knowledge was good. Husband's Support and Pregnant Women's Knowledge influenced ANC Visits at the Leo Leo Health Center. Gather pregnant women and husbands or families to provide counseling on the importance of ANC Visits and remind pregnant women and husbands to always read the KIA Book so that they know the importance of ANC Visits